2021
DOI: 10.4236/ape.2021.112012
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Physical Activity Levels amongst University Employees

Abstract: Approximately 60% of the world's population do not meet the physical activity (PA) guidelines. Physical inactivity is increasing in occupations, with work-related health issues becoming more prevalent. University employees' work in a range of job roles and PA levels in this population is unclear. Thus, this study aimed to evaluate PA levels amongst university employees in a UK Higher Education institution. Four hundred employees (male = 131, female = 269) partook in this quantitative study and completed an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
1
13
0
2
Order By: Relevance
“…Although employees spent most of their time being sedentary and this was consistent between genders, the findings indicated that females were spending a substantial amount of time being sedentary, which could undesirably affect their health and wellbeing. Overall, the outcome of this study in line with previous research supports the hypothesis that male were more active than females (Lindsay et al, 2016;Olney et al, 2018;Sallis et al, 2016;Safi et al, 2021). Further investigation to rationalise the comparative differences and reasons behind the discrepancies reported by males and females are required.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although employees spent most of their time being sedentary and this was consistent between genders, the findings indicated that females were spending a substantial amount of time being sedentary, which could undesirably affect their health and wellbeing. Overall, the outcome of this study in line with previous research supports the hypothesis that male were more active than females (Lindsay et al, 2016;Olney et al, 2018;Sallis et al, 2016;Safi et al, 2021). Further investigation to rationalise the comparative differences and reasons behind the discrepancies reported by males and females are required.…”
Section: Discussionsupporting
confidence: 89%
“…The significant differences between job roles shows that academic staff engaged in greater light PA and MVPA than the administration and professional services staff. This could be due to the job roles of academics as they were more likely to conduct light PA through their daily responsibilities, including walking to and from the lectures, practical sessions, and student engagement activities (Safi et al, 2021). Whereas, the administration and professional services staff are required to be presented at their desk, which may contribute to their lack of engagement in light PA and MVPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following an institutional ethical approval, participants were recruited via an opportunistic sample using those who had participated in earlier studies of a broader piece of research from a UK higher education institution (university workplace) [ 32 , 33 ]. From the original pool of 259 participants who signed up to be contacted, 221 employees (85%) replied expressing their interest in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 provides the breakdown of total participants who attended a focus group interviews. The inclusion criteria were that all participants had to be adults (>18 years old), currently employed by the participant university, and had participated in earlier studies [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%